The Language of Linguistic Research: Is there Room for Meaning Extension? - Šeškauskienė, Inesa (Kalbotyra, 2008)
Meaning extension, including metaphors and metonymies, has traditionally been associated with the language of fiction. Cognitive linguistics has given this area a new impetus by unravelling the metaphoricity of our everyday language and various discourses ranging from spoken to written, from learner language to academic or professional (legal, medical, political). Lakoff (1991 and 1995), Cienki (2005), Schmidt (2003), Cibulskienė (2006), Vaičenonienė (2002) and many other researchers seem to give preference to political and socio-economic discourse which has generated within this branch of linguistics a large amount of research all over the world.Academic discourse (AD) and its multiple layers of meaning, however, has received less attention since it is generally believed that AD aims at discovering the truth, explaining and arguing, it is rigid, critical and unambiguous. According to Hyland (2004, 87), AD depends upon the demonstration of absolute truth, empirical evidence or flawless logic. Its persuasive potency is seen as grounded in rationality and based on exacting methodologies, dispassionate observation, and informed reflection. (…) We see this form of persuasion as a guarantee of reliable knowledge, and we invest it with cultural authority, free of the cynicism with which we view the partisan rhetoric of politics and commerce.So this paper attempts to provide evidence for the claim that AD, like any other discourse, is equally inclined to meaning extension, specifically, metaphors and metonymies. The paper is structured around several key issues: first, it gives background to the study, including a discussion on academic discourse, its relation to other discourse types, the contrastive parameter of investigation and other methodological issues and second, it identifies major types of metonymical and metaphorical extensions as reflected in the data corpus and manifested in linguistic texts in English (EN) and Lithuanian (LT).